THE USE OF VISUAL RESPONSE SYMBOL TO IMPROVE STUDENTSâ SPEAKING FLUENCY IN SUMMARIZING READING TEXTS OF INTERMEDIATE 3 CLASS IN LB LIA PALEMBANG - RUSMIANA, RATY (Sriwijaya University Learning and Education International Conference, 2016)
to make and share meaning about reading text through the creation of visualrepresentations. This interpretative strategy, known as